GEGURITAN JOHARSA PUH 5 - 9 (Sebuah Kajian Terhadap Naskah Bali Klasik Bernuansa Keagamaan Islam) - Moh Amaluddin (Analisa: Journal of Social Science and Religion, 2008)
Islamic classic Balinese literature is one of past Balineseliteratures that contain Islamic thoughts, especially mysticism andmagnanimity. Characteristics of Islamic classic Balinese literatureare,for example, written in Balinese and rarely using Islamic aspects.Current research intended to analyze contents of Geguritan JoharsaPuh 5 until Puh 9 texts. The story presented in the text containlesson on praying. According to the author, God will answer aprayer sent by human beings by giving direction on what shouldthey do in order to achieve their goals. In addition, in facing failure,faithful human being still has changes to achieve their goals throughprayers.